2011
DOI: 10.1111/j.1530-0277.2011.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Feeding Accelerates Hepatocellular Carcinoma Progression in a Sex‐Dependent Manner in a Mouse Model of Hepatocarcinogenesis

Abstract: Background Chronic ethanol consumption increases the risk of hepatic cirrhosis and hepatocellular carcinoma (HCC). While sex differences exist in susceptibility to ethanol-induced liver damage-HCC development, little is known about the effects of ethanol on tumor progression. Methods Neonatal male and female mice were initiated with a single dose of diethylnitrosamine (DEN). 16 or 40 weeks later animals were placed on a 10/20% (v/v) ethanol-drinking water (EtOH-DW; alternate days) regime for 8 weeks. At stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 45 publications
3
85
0
1
Order By: Relevance
“…Introduction and maintenance on EtOH-DW with the CD regimen resulted in reduced tumor formation (44%) and no significant difference for those on a HFD. This is in contrast to previous results from our group utilizing the same EtOH-DW regimen in B6C3F1 mice, supporting inter-strain differences in susceptibility to hepatic tumor formation and progression, despite similar blood alcohol content levels (12–15 mM/L) in the two strains (Brandon-Warneret al, 2012b; Thompson et al, 2013). …”
Section: Microrna Profiling To Identify Promoters Of Hcc Progresssupporting
confidence: 46%
“…Introduction and maintenance on EtOH-DW with the CD regimen resulted in reduced tumor formation (44%) and no significant difference for those on a HFD. This is in contrast to previous results from our group utilizing the same EtOH-DW regimen in B6C3F1 mice, supporting inter-strain differences in susceptibility to hepatic tumor formation and progression, despite similar blood alcohol content levels (12–15 mM/L) in the two strains (Brandon-Warneret al, 2012b; Thompson et al, 2013). …”
Section: Microrna Profiling To Identify Promoters Of Hcc Progresssupporting
confidence: 46%
“…Tumor initiation results from ethanol (EtOH) metabolism by alcohol dehydrogenase and cytochrome P450 (CYP) 2E1 thus, producing acetaldehyde and reactive oxygen species which interfere with DNA synthesis and repair mechanisms, leading to mutagenicity and tumorigenesis (4, 11). In addition to initiating effects, EtOH also has proliferative and tumor promoting effects in the liver (7, 8, 12). Our laboratory has demonstrated that EtOH stimulates hepatocyte proliferation in rodents in association with liver injury and hepatic vitamin A depletion (13-15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that dietary intervention with soy may prevent EtOH-mediated tumor promoting effects by inhibiting β-catenin signaling and associated proliferation mechanisms. To test this hypothesis, we utilized a two-stage mouse model in which tumor initiation by a genotoxic compound, diethylnitrosamine (DEN), was followed by the promoting agent, an EtOH liquid diet (13,16, 29), containing either casein or soy protein isolate (SPI) as the sole source protein source. Administration of these diets continued for 16 wks, at which livers were analyzed for the presence of adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…This stage is characterized by release of TGF-β1, mostly by Kupffer cells 4 , and activation of Hepatic stellate cells (HSCs) 13,14 . Furthermore, a recent study has demonstrated that addition of ethanol to drinking water increased tumor incidence in DEN-injected male mice 15 , suggesting that this model can be used to study the effects of ethanol on HCC progression.…”
Section: Ald Progression In Patientsmentioning
confidence: 99%